Numerical Prediction of the Solidification and Melting of Encapsulated Nano-Enhanced Phase Change Materials - Vasco-Calle, D; Jonathan Jesus-Cofre, T (John Wiley and Sons Inc, 2024)
The thermal properties of Octadecane vary due to the addition of copper oxide (CuO) nanoparticles. The synthesis of two nano-enhanced phase change material (NEPCM) required the implementation of the two-step method, using Octadecane as the base phase change material and CuO nanoparticles at 2.5 and 5.0 wt%. The experimental characterization determined the specific heat capacity, and thermal conductivity of the NEPCMs solid phase, including phase change enthalpy and temperature. These experimental results were then utilized for computational simulation of the thermal charging (solidification) and discharging (melting) processes of NEPCMs within a spherical enclosure, employing the ANSYS/Fluent software. The incorporation of CuO nanoparticles led to an increase in thermal conductivity while causing a decrease in specific heat capacity, enthalpy, and phase change temperature of Octadecane. The computational results revealed a reduction in the melting period and an improvement in the solidification of both NEPCMs. In terms of melting, the convective heat transfer coefficient increased by approximately 27.4% and 3.2% for the NEPCM at 2.5 and 5.0 wt% CuO, respectively. During the solidification process, the overall heat transfer coefficient experienced a significant increase of 43.8% and 59.8% for the NEPCM at 2.5 and 5.0 wt%, respectively. © 2023 John Wiley & Sons Ltd.